2018
DOI: 10.1016/j.urolonc.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Black race predicts significant prostate cancer independent of clinical setting and clinical and socioeconomic risk factors

Abstract: Black race is independently associated with CaP and Gleason ≥3+4 CaP after accounting for clinical and socioeconomic risk factors including clinical setting and WAA, and has a higher odds ratio of CaP diagnosis in younger men. Further investigation into optimizing screening in Black men aged 40 to 54 is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…Interestingly, in a study of 244 AA men from Chicago, Kittles and coworkers also found that % WA ancestry was associated with a higher risk of cancer on standard 12 core biopsy, but did not find an association between % WA ancestry and Gleason sum . A subsequent study of 287 Chicago‐area prostate biopsy patients found that WA ancestry was not predictive of cancer or GS 7‐10 cancer on biopsy . Both of the Chicago studies used the same panel of ancestry genetic markers as used in our study of patients from Birmingham Alabama and, as expected, the median WA ancestry observed in the Birmingham patients (median 82.2, IQR 73.5‐88.4) is greater than the median reported in the Chicago patients (median 78.4, IQR 69.7‐92.2 and median 80.4; IQR 70.4‐86.4 for Nyame et al and Nettey et al respectively).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Interestingly, in a study of 244 AA men from Chicago, Kittles and coworkers also found that % WA ancestry was associated with a higher risk of cancer on standard 12 core biopsy, but did not find an association between % WA ancestry and Gleason sum . A subsequent study of 287 Chicago‐area prostate biopsy patients found that WA ancestry was not predictive of cancer or GS 7‐10 cancer on biopsy . Both of the Chicago studies used the same panel of ancestry genetic markers as used in our study of patients from Birmingham Alabama and, as expected, the median WA ancestry observed in the Birmingham patients (median 82.2, IQR 73.5‐88.4) is greater than the median reported in the Chicago patients (median 78.4, IQR 69.7‐92.2 and median 80.4; IQR 70.4‐86.4 for Nyame et al and Nettey et al respectively).…”
Section: Discussionsupporting
confidence: 57%
“…15 A subsequent study of 287 Chicago-area prostate biopsy patients found that WA ancestry was not predictive of cancer or GS 7-10 cancer on biopsy. 16 Comparing the relative prevalence of PrCa risk loci in AAs in Birmingham and Chicago might identify subtypes of PrCa that are more common in some AA communities than in others. In addition, an examination of potential interactions between WA ancestry and nongenetic risk factors, like obesity that are more prevalent in AAs in the South than in other parts of the US 18 may reveal modifiable variables that can be incorporated into interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-cohort study of 306,100 patients with prostate cancer did not find any significant association between black ethnicity and the disease [ 21 ]. However, Nettey et al [ 22 ] revealed that the frequency of prostate cancer was high in the black population compared to the non-black population. The results of a meta-analysis by Adeloye et al [ 23 ] showed a median incidence rate of prostate cancer of 19.5/100,000 in a population from the African region, which was higher when compared to Asian [ 15 ], European [ 24 ], or American populations.…”
Section: Prostate Cancer—etiology and Pathogenesismentioning
confidence: 99%
“…For black men during the same time period, it is expected that prostate cancer will account for approximately 30% of all new cancer cases and 15% of all cancer deaths, one of the largest racial disparities of any cancer type [ 2 ]. Even when adjusting for clinical and socioeconomic risk factors, black men have a disproportionate burden of aggressive prostate cancer [ 3 ], suggesting that biological factors may also contribute.…”
Section: Introductionmentioning
confidence: 99%